Sierra Leone Multiple Indicator Cluster Survey 2017 - Statistics Sierra Leone (Statistics Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:7794TCGJ 2405685:N9SALPUS

Redesigning an education project for child friendly radio: a multisectoral collaboration to promote children’s health, education, and human rights after a humanitarian crisis in Sierra Leone - Barnett, Sarah; van Dijk, Jetske; Swaray, Abdulai; Amara, Tamba; Young, Patricia (BMJ, 2018)
Sarah Barnett and colleagues describe how an educational project was rapidly adapted into a radio education programme after the 2014 Ebola epidemic in Sierra Leone
shortDOI: 10/ggqvr7 KerkoCite.ItemAlsoKnownAs: 10.1136/bmj.k4667 10/ggqvr7 2339240:6IXLT92N 2405685:6Z36JH5J 2405685:S35X3HD9

Education Sector Plan, 2018-2020: Getting It Right – Service Delivery, Integrity and Learning in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:AIISD4KD 2405685:DFHS5ZVL

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Sierra Leone) (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:GVAZB6TM

Education Sector Plan 2018-2020 - Ministry of Education, Science and Technology (Sierra Leone) (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:24PRFKEK

Sierra Leone Media Landscape Report - BBC Media Action (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:7N6UW9TG 2405685:644SZI8D

GSMA Mobile Connectivity Index | Sierra Leone - GSMA (2018)
The GSMA Mobile Connectivity Index is a global mobile connectivity and digital economy guide covering 150 countries and 7 sub-regions
Library Catalog: www.mobileconnectivityindex.com EdTechHub.ItemAlsoKnownAs: 2405685:AGNKXIPC

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Wright, Dr. Cream (Global Partnership for Education; World Bank, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:9VRVIUE6 2405685:UU3R28HB

FQSE – Free Quality School Education - Ministry of Basic and Senior Secondary Education Sierra Leone (Ministry of Basic and Senior Secondary Education Sierra Leone, Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:XL83AVZI 2405685:7NLKWES7

Keynote Address by His Excellency President Julius Maada Bio on the theme of: "Education for Development" at the launch of the Free Quality School Education Programme - Maada Bio, Julius (2018)
KerkoCite.ItemAlsoKnownAs: 2339240:5TSMLUKK 2405685:FW7MT9FE

Sierra Leone population 2020 - WorldPop (2018)
RF-based gridded population distribution datasets produced in the framework of the Global Project - Funded by The Bill and Melinda Gates Foundation (OPP1134076)
KerkoCite.ItemAlsoKnownAs: 10.5258/SOTON/WP00645 2339240:2AJ3LMLD 2405685:92787LQS
Keywords: Population distribution; Population; Dasymetric disaggregation

Education for Development - Maada Bio, Julius (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:KL7FDUU7

Proportion of schools with access to basic facilities, all schools - UNESCO (2018)
EdTechHub.ItemAlsoKnownAs: 2405685:ZV8MELAV

Mobile Learning Lab Evaluation & Analysis - 60 Million Girls (60 million girls, 2018)
Library Catalog: 60millionsdefilles.org EdTechHub.ItemAlsoKnownAs: 2405685:ZPG2W382

Leh Wi Learn - Sierra Leone Secondary Education Improvement Programme - DFID (2018)
KerkoCite.ItemAlsoKnownAs: 2405685:9PJP3ZYU

Incidence of malaria (per 1,000 population at risk) - Sierra Leone, Sub-Saharan Africa (excluding high income) | Data - World Bank (2018)
KerkoCite.ItemAlsoKnownAs: 2129771:6RCWKTSF 2405685:7HILUDQR 4556019:XR5GKQEB

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Teaching Service Commission (Global Partnership for Education, 2018)
KerkoCite.ItemAlsoKnownAs: 2405685:CFRE6D4Q

The Economic Lives of Young Women in the Time of Ebola: Lessons from an Empowerment Program - Bandiera, Oriana; Buehren, Niklas; Goldstein, Markus; Rasul, Imran; Smurra, Andrea (World Bank, 2018)
We evaluate an intervention to raise young women’s economic empowerment in Sierra Leone, where women frequently experience sexual violence and face multiple economic disadvantages. The intervention provides them with a protective space (a club) where they can …nd support, receive information on health/reproductive issues and vocational training. Unexpectedly, the post-baseline period coincided with the 2014 Ebola outbreak. Our analysis leverages quasi-random across-village variation in the severity of Ebola-related disruption, and random assignment of villages to the intervention to document the impact of the Ebola outbreak on the economic lives of 4 700 women tracked over the crisis, and any ameliorating role played by the intervention. In highly disrupted control villages, the crisis leads younger girls to spend signi…cantly more time with men, out-of-wedlock pregnancies rise, and as a result, they experience a persistent 16pp drop in school enrolment post-crisis. These adverse e¤ects are almost entirely reversed in treated villages because the intervention enables young girls to allocate time away from men, preventing out-of-wedlock pregnancies and enabling them to re-enrol in school post-crisis. In treated villages, the unavailability of young women leads some older girls to use transactional sex as a coping strategy. The intervention causes them to increase contraceptive use so this does not translate into higher fertility. Our analysis pinpoints the mechanisms through which the severity of the aggregate shock impacts the economic lives of young women, and shows how interventions in times of crisis can interlink outcomes across younger and older cohorts. JEL Classi…cation: I25, J13, J24.
shortDOI: 10/ghgngq KerkoCite.ItemAlsoKnownAs: 10.1596/1813-9450-8760 10.1596/31219 10/ghgngn 10/ghgngq 2339240:P9QQ2FKF 2405685:2TEE6A8C 2405685:BA7ISGH3
Keywords: ___working_potential_duplicate

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Government of Sierra Leone; UNICEF, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:843DCCS6 2405685:HZ89SJYF

Mission and Vision - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education Republic of Sierra Leone, Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:PM4PUYXJ 2405685:LI99LYJA

Statement from the Minister - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education, Government of Sierra Leone, 2018)
KerkoCite.ItemAlsoKnownAs: 2339240:QIYCJQ6B 2405685:7G2FJMLB

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found